A novel hydrogel loaded with plant exosomes and stem cell exosomes as a new strategy for treating diabetic wounds - Jialu Weng; Yizhang Chen; Yuhan Zeng; Wenzhang Jin; Ying Ji; Wa Zhang; Shunfu Wang; Haobing Li; Meilin Yi; Xiaoying Niu; Xuchen Deng; Jiancheng Huang; et al. (Materials Today Bio)
Diabetic wound healing is constrained by various factors, including chronic inflammation, sustained oxidative stress, impaired angiogenesis, and abnormal wound microenvironments. Exosomes derived from mesenchymal stem cells (MSC-exo) contain a wealth of bioactive substances that play a positive role in promoting diabetic wound healing. Plant-derived exosomes, as a novel therapeutic approach, are continuously being explored. Momordica charantia (MC) has been shown to possess blood glucose-lowering effects, and its exosomes are of significant relevance for treating diabetic wounds. However, direct application of exosomes to wounds faces challenges such as poor stability and short retention time, limiting their therapeutic effectiveness and clinical applicability. Encapsulating exosomes in hydrogels is an effective strategy to preserve their bioactivity. In this study, we fabricated a hydrogel loaded with MSC-exo and MC exosomes (MC-exo) by photopolymerization of methacrylated gelatin (GelMA) and dopamine (MEMC-Gel). The resulting MEMC-Gel exhibited favorable mechanical properties, adhesion, degradability, absorbency, and biocompatibility. In vitro, MEMC-Gel demonstrated the ability to resist inflammation, counter oxidative stress, promote fibroblast migration, support endothelial cell angiogenesis, and regulate macrophage polarization. In a diabetic mouse wound model, MEMC-Gel accelerated wound healing by inhibiting inflammation and oxidative stress, modulating macrophage immune responses and hyperglycemia within the microenvironment, promoting angiogenesis, and enhancing epithelialization. In conclusion, MEMC-Gel is an outstanding hydrogel dressing that synergistically promotes repair by loading MSC-exo and MC-exo, significantly accelerating diabetic wound healing through multiple mechanisms. This multifunctional hydrogel, based on exosomes from two different sources, provides an innovative therapeutic strategy for diabetic wound repair with broad clinical application potential.